Generating beneﬁcial predator genomes to provide comparative insights into insecticide resistance-related gene families. - Bailey, Emma (Cranfield University, 2022)
With a rapidly growing population to feed, ﬁnding ways to increase crop yields has become more important than ever. Insect pests contribute hugely to yield losses every year and ﬁnding methods to effectively control pest levels is therefore crucial to reduce these losses. Insecticide use alone is no longer a viable solution, due to ever increasing levels of resistance developing amongst crop pests, as well as the environmental concerns associated with their overuse. Biological control – the use of natural predators to keep pest populations under control – has proven to be a highly effective method of pest control and generally has less severe environmental impacts than pesticides (although introducing non-native species can result in undesirable changes to local biodiversity). Biological control agents are therefore a key component of Integrated Pest Management (IPM) strategies, which aim to manage pest populations in a sustainable and economical manner. IPM programs prioritise selective insecticides which target the pest species and are harmless to the beneﬁcial predators. However, the numbers of reported insecticide resistance cases are far lower in beneﬁcial predators as opposed to crop pests. As a result, insecticide application often harms beneﬁcial predator populations and reduces their biological control capabilities, which may allow resistant pest populations to surge after application. Genomic information is readily available for a multitude of crop pest species, however, when this project began, there was minimal genomic data available for beneﬁcial predators. By increasing the availability of genomic data for beneﬁcial predators, we can perform comparative analyses between crop pests and their predators of insecticide target-sites and genes encoding metabolic enzymes potentially responsible for insecticide resistance. These analyses may help uncover whether there is any genomic basis for the reduced number of insecticide resistance cases in beneﬁcial predators compared to crop pests. The aim of this project was to ﬁrstly sequence and assemble the genomes of key beneﬁcial predators for which no genomic information is currently available. This included Orius laevigatus (minute pirate bug), Sphaerophoria rueppellii (European hoverﬂy) and Microctonus brassicae (parasitoid wasp). Next, these genomes were annotated and manual curation of resistance-associated detoxiﬁcation genes was performed. The resultant detoxiﬁcation gene sets were then used to perform comparative analyses between beneﬁcial predators and crop pests. The results from the comparative analysis suggest a greater degree of detoxiﬁcation family gene expansion within crop pests compared to beneﬁcial predators. This difference was particularly apparent in the families associated with detoxiﬁcation of plant xenobiotics and suggests that the plant-based diet of crop pests provided increased selection pressure for resistance mechanisms prior to the introduction of insecticides. Once insecticides were introduced, crop pests may therefore have had an advantage over beneﬁcial predators in terms of developing insecticide resistance. In addition, variation in the levels of resistance between different beneﬁcial predators correlated to some extent with gene expansion, with several factors having likely had some inﬂuence on this, including diet, migration and length of commercial use. The knowledge gained from this project could contribute to our understanding of insecticide resistance from a genomic perspective and aid in the development of successful IPM strategies.
Keywords: crop yields; insect pests; environmental impact; biodiversity; beneficial predators; genomic data